Chance fracture of the lumbar spine in an amateur snowboarder: a case report - Hakozaki, M.; Otani, K.; Kikuchi, S.; Konno, S. (The Journal of Sports Medicine and Physical Fitness, 2010)
"Chance fracture" is an unusual type of spinal fracture caused by flexion-distraction of the back. We describe herein a rare case of a male amateur snowboarder who suffered lumbar Chance fracture caused by a fall after freestyle jumping. Radiological findings of plain radiography, computed tomography (CT), and magnetic resonance imaging (MRI) showed a loss of vertebral height in the anterior L1 vertebral body with a horizontal splitting fracture extending across the vertebral body, bilateral pedicles, and lamina. On the basis of the aforementioned findings, the diagnosis of Chance fracture of the L1 vertebra was established. The fracture healed without any subsequent disabilities following conservative medical management with a thoracolumbar orthosis, and no impairments to activities of daily living were encountered, including job or sports performance. Although Chance fracture caused by a fall is rare, particularly in sports, the possibility of this fracture should be considered when diagnosing spinal injuries in snowboarders.